Weight training in youth-growth, maturation, and safety: an evidence-based review - Malina, R. (Clinical Journal of Sport Medicine, 2006)
Objective: To review the effects of resistance training programs on pre- and early-pubertal youth in the context of response, potential influence on growth and maturation, and occurrence of injury.